The combined effects of filter-feeding bivalves (Cristaria plicata) and submerged macrophytes (Hydrilla verticillate) on phytoplankton assemblages in nutrient-enriched freshwater mesocosms - Du, Xue; Song, Dan; Wang, Huibo; Yang, Jingshuang; Liu, Hui; Huo, Tangbin (Frontiers in Plant Science, 2023)
Freshwater ecosystems are threatened by eutrophication, which causes persistent and harmful algal blooms. Filter-feeding bivalve mollusks and submerged macrophytes (SMs) alleviate the eutrophication effects by inhibiting phytoplankton biomass blooms. However, very little is known about whether and how the combined manipulation of filter-feeding bivalves and SMs control eutrophication and influence phytoplankton assemblages. Here, we performed a nutrient-enriched freshwater mesocosm experiment to assess the combined effects of the filter-feeding bivalve Cristaria plicata, a cockscomb pearl mussel, and the macrophyte Hydrilla verticillate on the biomass and composition of phytoplankton assemblages. We found that addition of C. plicata and H. verticillate decreased the water nutrient concentrations and suppressed overall phytoplankton biomass. Further, distinct differences in taxa between restoration and control treatments were observed and noticeably competitive exclusion of cyanobacteria in the restoration treatments occurred. An antagonistic interaction between filter-feeding bivalves and SMs was only detected for total cyanobacteria biomass demonstrating that a larger magnitude of SM restoration may override the effect of filter-feeding bivalves. Our results suggest that biomanipulation, through the addition of bivalves as grazers, associated with the restoration of SMs, is an efficient approach for reducing cyanobacterial blooms and alleviating eutrophication.